Screening, diagnosis, and management of patients with Fabry disease: conclusions from a “Kidney Disease: Improving Global Outcomes” (KDIGO) Controversies Conference - Schiffmann, Raphael; Ries, Markus (Kidney international, 2017)
Patients with Fabry disease (FD) are at a high risk for developing chronic kidney disease and cardiovascular disease. The availability of specific but costly therapy has elevated the profile of this rare condition. This KDIGO conference addressed controversial areas in the diagnosis, screening, and management of FD, and included enzyme replacement therapy and nonspecific standard-of-care therapy for the various manifestations of FD. Despite marked advances in patient care and improved overall outlook, there is a need to better understand the pathogenesis of this glycosphingolipidosis and to determine the appropriate age to initiate therapy in all types of patients. The need to develop more effective specific therapies was also emphasized.
Other Conference participants Daniel G. Bichet, Canada; Erik Ilsø Christensen, Denmark; Ricardo Correa-Rotter, Mexico; Perry M. Elliott, UK; Sandro Feriozzi, Italy; Agnes B. Fogo, USA; Dominique P. Germain, France; Carla E.M. Hollak, Netherlands; Robert J. Hopkin, USA; Jack Johnson, USA; Ilkka Kantola, Finland; Jeffrey B. Kopp, USA; Jürgen Kröner, Germany; Ales Linhart, Czech Republic; Ana Maria Martins, Brazil; Dietrich Matern, USA; Atul B. Mehta, UK; Renzo Mignani, Italy; Behzad Najafian, USA; Ichiei Narita, Japan; Kathy Nicholls, Australia; Greg T. Obrador, Mexico; João Paulo Oliveira, Portugal; Antonio Pisani, Italy; Juan Politei, Argentina; Uma Ramaswami, UK; Markus Ries, Germany; Wim Terryn, Belgium; Camilla Tøndel, Norway; Roser Torra, Spain; Bojan Vujkovac, Slovenia; Stephen Waldek, UK; Jerry Walter, USA
Available online 18 December 2016
Gesehen am 17.04.2019